Slow rate of secondary forest carbon accumulation in the Guianas compared with the rest of the Neotropics. Issue 1 (18th October 2019) - Chave, Jérôme; Piponiot, Camille; Maréchaux, Isabelle; de Foresta, Hubert; Larpin, Denis; Fischer, Fabian Jörg; Derroire, Géraldine; Vincent, Grégoire; Hérault, Bruno
Abstract: Secondary forests are a prominent component of tropical landscapes, and they constitute a major atmospheric carbon sink. Rates of carbon accumulation are usually inferred from chronosequence studies, but direct estimates of carbon accumulation based on long‐term monitoring of stands are rarely reported. Recent compilations on secondary forest carbon accumulation in the Neotropics are heavily biased geographically as they do not include estimates from the Guiana Shield. We analysed the temporal trajectory of aboveground carbon accumulation and floristic composition at one 25‐ha secondary forest site in French Guiana. The site was clear‐cut in 1976, abandoned thereafter, and one large plot (6.25 ha) has been monitored continuously since. We used Bayesian modeling to assimilate inventory data and simulate the long‐term carbon accumulation trajectory. Canopy change was monitored using two aerial lidar surveys conducted in 2009 and 2017. We compared the dynamics of this site with that of a surrounding old‐growth forest. Finally, we compared our results with that from secondary forests in Costa Rica, which is one of the rare long‐term monitoring programs reaching a duration comparable to our study. Twenty years after abandonment, aboveground carbon stock was 64.2 (95% credibility interval 46.4, 89.0) Mg C/ha, and this stock increased to 101.3 (78.7, 128.5) Mg C/ha 20 yr later. The time to accumulate one‐half of the mean aboveground carbon stored in the nearby old‐growth forest (185.6 [155.9, 200.2] Mg C/ha) was estimated at 35.0 [20.9, 55.9] yr. During the first 40 yr, the contribution of the long‐lived pioneer species Xylopia nitida, Goupia glabra, and Laetia procera to the aboveground carbon stock increased continuously. Secondary forest mean‐canopy height measured by lidar increased by 1.14 m in 8 yr, a canopy‐height increase consistent with an aboveground carbon accumulation of 7.1 Mg C/ha (or 0.89 Mg C·ha −1 ·yr −1 ) during this period. Long‐term AGC accumulation rate in Costa Rica was almost twice as fast as at our site in French Guiana. This may reflect higher fertility of Central American forest communities or a better adaptation of the forest tree community to intense and frequent disturbances. This finding may have important consequences for scaling‐up carbon uptake estimates to continental scales.